EFL pre-service teachers’ excessive use of Google Translate: Blessing or misfortune? - Atin Kurniawati; Arief Eko Priyo Atmojo (Universitas Negeri Semarang, 2025)
This study investigates EFL pre-service teachers’ use of Google Translate (GT) on a daily basis under three underlying questions: 1) Why do EFL pre-service teachers often use GT? 2) How do they use it on a daily basis? and 3) What are the drawbacks of using GT? Despite its benefits, debates over its use in educational settings remain a prevailing issue. For this reason, a case study approach involving six EFL pre-service teachers in different semesters was employed. To garner the data, an open-ended questionnaire and an interview that was done in several sessions were deployed. Thematic analysis was then utilized to analyze the data. The findings reveal that the EFL pre-service teachers’ excessive use of GT was caused by their lack of vocabulary, pronunciation, and grammar. Quick and easy use of GT and lack of confidence to express their own sentences also encouraged them to use GT excessively. They used GT on a daily basis for both academic and non-academic purposes. They also incorporated GT with other applications, especially for doing academic assignments, since they realized that GT was sometimes unreliable. Their background knowledge of English played an important role in examining the translation results of GT. The EFL pre-service teachers have been aware that using GT excessively could decrease their learning ability, and they should enhance their English proficiency to effectively use GT. It implies that GT can assist EFL pre-service teachers’ learning by primarily deploying their own knowledge and skills and only utilizing GT for enhancement.